Optimization of approaches to the treatment of mild to moderate ulcerative colitis - S. S. Belous; O. V. Knyazev (Лечащий Врач)
Ulcerative colitis is an autoimmune disease of the colon, manifested by the development of non-specific inflammation of its mucous membrane with a mandatory lesion of the rectum. The most common in clinical practice is left-sided ulcerative colitis, a mild or moderate attack. The optimal treatment for such patients is mesalazine, but the use of the drug with a pH-dependent shell may be limited due to the large variety of pH values in patients with inflammatory bowel diseases. The drugs of choice in such situations are ethylcellulose-coated mesalazine microgranules with prolonged release, which allow to achieve the maximum therapeutic effect. To improve the results of mesalazine therapy, the combined use of a local and systemic drug is necessary. If this approach is ineffective, the use of budesonide MMH may be considered as an alternative to systemic glucocorticosteroids.